2013
DOI: 10.1177/1077546313501186
|View full text |Cite
|
Sign up to set email alerts
|

Passivity-based chaos control and synchronization of the four dimensional Lorenz-Stenflo system via one input

Abstract: This paper discusses chaos control and synchronization of the four dimensional Lorenz-Stenflo system based on passive control technique. Using passive theory, chaos control and synchronization of a four dimensional Lorenz-Stenflo chaotic system are realized with one input. The designed controllers ensure the stability of the controlled system and error dynamical system between two identical Lorenz-Stenflo systems. Also, the controllers ensure that the controlled system and error dynamical system converge to ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…0 and _ W ðzÞ 0, it can be concluded that W ðzÞ is the Lyapunov function of f 0 ðzÞ and that f 0 ðzÞ is globally asymptotically stable. 25 So, the zero dynamics of Vilnius chaotic system is stable with the Lyapunov's method. The controlled system can be equivalent to a passive system and globally asymptotically stabilized at its zero equilibrium by the following state feedback controller 24 :…”
Section: Synchronization Of Vilnius Chaotic Systems Using Passive Conmentioning
confidence: 99%
See 3 more Smart Citations
“…0 and _ W ðzÞ 0, it can be concluded that W ðzÞ is the Lyapunov function of f 0 ðzÞ and that f 0 ðzÞ is globally asymptotically stable. 25 So, the zero dynamics of Vilnius chaotic system is stable with the Lyapunov's method. The controlled system can be equivalent to a passive system and globally asymptotically stabilized at its zero equilibrium by the following state feedback controller 24 :…”
Section: Synchronization Of Vilnius Chaotic Systems Using Passive Conmentioning
confidence: 99%
“…Since the seminal work by Pecora and Carroll, the synchronization and control in chaotic systems have caught a lot of attention among scientists. Various techniques have been used for the synchronization of chaotic systems, such as active control, [17][18][19][20][21] passive control, [22][23][24][25] linear feedback control, 26 nonlinear control, 27 sliding mode control, 28 backstepping control, 21 impulsive control, 29 and so on. Synchronization using active control was introduced by Bai and Lonngren using Lorenz system in 1997 17 and later it has been implemented for the synchronization of other chaotic systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we will study the chaotic behavior and control of (1) under two-frequency perturbations. We study the bifurcation and dynamical behaviors depending on the parameters by using bifurcation and chaos theories in [15][16][17][18][19][20][21] and numerical simulation. By applying Melnikov method [15,20,21], we prove the criterion of existence of chaos under periodic perturbation.…”
Section: Introductionmentioning
confidence: 99%